The Roles of Carcinoembryonic Antigen in Liver Metastasis and Therapeutic Approaches - Joo Han Lee; Seong-Wook Lee (Gastroenterology Research and Practice)
Metastasis is a highly complicated and sequential process in which primary cancer spreads to secondary organic sites. Liver is a well-known metastatic organ from colorectal cancer. Carcinoembryonic antigen (CEA) is expressed in most gastrointestinal, breast, and lung cancer cells. Overexpression of CEA is closely associated with liver metastasis, which is the main cause of death from colorectal cancer. CEA is widely used as a diagnostic and prognostic tumor marker in cancer patients. It affects many steps of liver metastasis from colorectal cancer cells. CEA inhibits circulating cancer cell death. CEA also binds to heterogeneous nuclear RNA binding protein M4 (hnRNP M4), a Kupffer cell receptor protein, and activates Kupffer cells to secrete various cytokines that change the microenvironments for the survival of colorectal cancer cells in the liver. CEA also activates cell adhesion-related molecules. The close correlation between CEA and cancer has spurred the exploration of many CEA-targeted approaches as anticancer therapeutics. Understanding the detailed functions and mechanisms of CEA in liver metastasis will provide great opportunities for the improvement of anticancer approaches against colorectal cancers. In this report, the roles of CEA in liver metastasis and CEA-targeting anticancer modalities are reviewed.